Information Content Hypotesis Pada Saham Terindeks JII - Yayu Putri Senjani; Randi Irawan Wibantoro (Akuntabilitas, 2018)
This research aims to test Information Content Hypothesis of Jakarta Islamic Index (JII) for stock prices. Two Independent Samples T-Test is used to test the difference of 195 stock prices in 39 companies entering and leaving the 5 JII lists during 2015-2017. The result is that there are differences of stock prices when company is listed compared to the stock prices when the company is taken out in the JII list. The companies have higher stock prices when it entered than when it is excluded in JII.